An Agent-Based Model of an Online Collaboration Community by using Fuzzy Logic. Issue 13 (2019) - Olcay, Ertug; Schöttl, Claus; Khalid, Ans; Zaggl, Michael A.; Lohmann, Boris
Abstract: Manufacturing companies increasingly use online collaboration communities to generate ideas and solutions. This paper suggests a modeling approach for such an online community. It analyzes the task solving behavior and the evolution of its average commitment level. Communities are influenced by many attributes such as individual demands, skills, and activities of members. Due to this heterogeneity the modeling of such a system is not a simple task. The agent-based model helps to predict system behavior and proposes measures for online community management. Agent-based models help to analyze theories and perspectives regarding social systems. In this study, we design the dynamics of a conceptual online collaboration community by combining the agent-based modeling technique with fuzzy logic. We model an interesting phenomenon in an online community from a dynamic perspective.